PENGARUH KUALITAS LAYANAN, NILAI PELANGGAN, CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN - Wangkar, Anneke (Universitas Sam Ratulangi, 2013)
This study aims for know the influence of Quality Service, Value Customer, Customer Relationship Management (CRM) against Satisfaction Customer and Customer Loyalty PT. William Makmur Perkasa as an parties who sublease heavy equipment. Population is customer tenant heavy equipment which amount to 88 customer with technique sampling which used is sensus. Data is obtained by way of using questionnaires and documentation. Technique data analysis using analysis pathways (Path Analysis). The results of research showed that the Variable Value Customer (X2) has a significant influence and positive towards variable Customer Satisfaction (Y1). Variable Quality of Service (X1) has a positive influence signifikan to variable Customer Loyalty (Y2). Variabel Customer Value (X2) has a positive influence signifikan to variable Customer Loyalty (Y2), Variabel CRM (X3) has a positive influence signifikan to variable Customer Loyalty (Y2). Variable Satisfaction Customer (Y1) has a positive signifikan to variable Customer Loyalty (Y2). Based on the conclusion the research then it can advisable things as follows : Company in this case PT. William Makmur Perkasa must pay attention to pathways who significant in this research in order that so that can be add to and retain customer with better. Keywords : Service Quality, Customer Value, Customer Relationship Management (CRM) Customer Satisfaction and Customer Loyalty